Wpływ ruchu przygranicznego na aktywizację polskiej części euroregionu Glacensis - Oparka, Sylwia (The Influence of the Border Area Traffic on Activating Polish Part of Glacensis Euroregion, 2005)
In the 20s of the XX century there was observed an increase in the border area traffic volume at all Polish borders. This phenomenon was accompanied by an increased trading activity, especially with regard to Polish western border, but also the southern one. Such activities turned out to be an important stimulating factor enhancing cross-border cooperation, an example of which bas become the Glacensis Euroregion. The hereby article attempts to identify factors which influence the development of traffic along the border areas in the discussed euroregion, as well as the resulting advantages for communes of the Polish part of the Glacensis Euroregion. There are also defined activities which may lead towards further development of cross-border traffic in this area.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1067, s. 141-157